Detection of Echinococcus multilocularis by MC-PCR: evaluation of diagnostic sensitivity and specificity without gold standard. Issue 1 (1st January 2016) - Wahlström, Helene; Comin, Arianna; Isaksson, Mats; Deplazes, Peter
Abstract : Introduction: A semi-automated magnetic capture probe-based DNA extraction and real-time PCR method (MC-PCR), allowing for a more efficient large-scale surveillance of Echinococcus multilocularis occurrence, has been developed. The test sensitivity has previously been evaluated using the sedimentation and counting technique (SCT) as a gold standard. However, as the sensitivity of the SCT is not 1, test characteristics of the MC-PCR was also evaluated using latent class analysis, a methodology not requiring a gold standard. Materials and methods: Test results, MC-PCR and SCT, from a previous evaluation of the MC-PCR using 177 foxes shot in the spring ( n =108) and autumn 2012 ( n =69) in high prevalence areas in Switzerland were used. Latent class analysis was used to estimate the test characteristics of the MC-PCR. Although it is not the primary aim of this study, estimates of the test characteristics of the SCT were also obtained. Results and discussion: This study showed that the sensitivity of the MC-PCR was 0.88 [95% posterior credible interval (PCI) 0.80–0.93], which was not significantly different than the SCT, 0.83 (95% PCI 0.76–0.88), which is currently considered as the gold standard. The specificity of both tests was high, 0.98 (95% PCI 0.94–0.99) for the MC-PCR and 0.99 (95% PCI 0.99–1) for the SCT. In a previous study, using fox scats from a low prevalence area, the specificity of the MC-PCR was higher, 0.999% (95% PCI 0.997–1). One reason for the lower estimate of the specificity in this study could be that the MC-PCR detects DNA from infected but non-infectious rodents eaten by foxes. When using MC-PCR in low prevalence areas or areas free from the parasite, a positive result in the MC-PCR should be regarded as a true positive. Conclusion: The sensitivity of the MC-PCR (0.88) was comparable to the sensitivity of SCT (0.83).